ON AND OFF - LINE QUALITY CONTROL FOR PRODUCT DESIGN AND MANUFACTURING PROCESSES - Onwubolu, Godfrey C. (The South African Journal of Industrial Engineering, 2011)
The Taguchi methodology which may be applied as off-line quality control in the product design stage or, as on-line quality control during production is presented. As an off-line quality improvement strategy, it is a preventive measure at the product or manufacturing systems design stage which has the capability of making the product design robust. As an on-line quality improvement strategy, it assists in diagnosing the cause of the variation during production for the purpose of either eliminating the cause of variation or redesigning the product/process to make the product robust against the effect of the variation. The results of a case study presented using a computer program developed show that the Taguchi methodology can lead to substantial improvements.